NOTES ON GEOGRAPHIC DISTRIBUTION: POTTIACEAE, HYOPHILA INVOLUTA (HOOK.) JAEG. & SAUERB. (NEW OCCURRENCE IN THE STATE OF MARANHÃO, BRAZIL), HYOPHILA APICULATA FLEISCH (NEW OCCURRENCE IN BRAZIL) - Brito, Eliete da Silva; da Conceição, Gonçalo Mendes; Peralta, Denilson Fernandes (PESQUISA EM FOCO, 2009)
Hyophila involuta (Hook.). Jaeg, is therefore considered a NEW OCORRENCE FOR THE STATE OF MARANHÃO, placing this state in the geographic distribution of this species in Brazil. Hyophila apiculata Fleisch, is a NEW OCORRENCE FOR BRAZIL, increasing from 20 to 21 the species in the genus Hyophila in Brasil. This also increases the number of species of the family Pottiaceae in Brasil from 132 to 133 species. New collection efforts should be undertaken to increase the knowledge of the bryoflora in the State of Maranhão and in Brazil.